Synthesis of isoeugenol biobased epoxy polymer by forming α‐hydroxyl ester and degradation studies. Issue 12 (1st November 2021) - Sivanesan, Dharmalingam; Seo, Bongkuk; Lim, Choong‐Sun; Song, Jinyoung; Kim, Hyeon‐Gook
Abstract: The synthesis of bio‐based monomers and polymers from renewable feedstock, such as plant biomass, is desirable because of the depletion of fossil fuel resources and the reliance of thermosetting epoxy resin on non‐renewable petrochemical monomers. Despite the excellent polymeric properties of bisphenol‐based epoxy resins, these negatively impact human health. Herein, the synthesis of self‐curable epoxy polymers from the bio‐based material isoeugenol by forming α‐hydroxyl esters is reported. The epoxides are named AB (single epoxide and ester groups) and A2B2 (double epoxide and ester groups), based on the number of active ester and epoxide groups. The materials derived from the bio‐based material, AB and A2B2, were initiated with and without the catalyst N, N ′‐dimethylaminopyridine (DMAP) and curing agent diaminodiphenylmethane. Without the catalyst, AB and A2B2 self‐polymerized at 247 and 210°C, respectively. Notably, the polymerization temperatures for AB and A2B2 decreased after the addition of DMAP. The self‐cured epoxy resin without the catalyst showed the highest thermal stability and glass transition temperature ( T g  = 156°C). Degradation and recovery studies suggested forward that 51% of the material could be recovered and 94% of the polymer could be degraded from the self‐cured A2B2 in 25 wt% NaOH solution. Abstract :